The role of SIRT1 in skeletal muscle function and repair of older mice. Issue 4 (14th June 2019) - Myers, Matthew J.; Shepherd, Danielle L.; Durr, Andrya J.; Stanton, David S.; Mohamed, Junaith S.; Hollander, John M.; Alway, Stephen E.
Abstract: Background: Sirtuin 1 (SIRT1) is a NAD+ sensitive deacetylase that has been linked to longevity and has been suggested to confer beneficial effects that counter aging‐associated deterioration. Muscle repair is dependent upon satellite cell function, which is reported to be reduced with aging; however, it is not known if this is linked to an aging‐suppression of SIRT1. This study tested the hypothesis that Sirtuin 1 (SIRT1) overexpression would increase the extent of muscle repair and muscle function in older mice. Methods: We examined satellite cell dependent repair in tibialis anterior, gastrocnemius, and soleus muscles of 13 young wild‐type mice (20–30 weeks) and 49 older (80+ weeks) mice that were controls ( n = 13), overexpressed SIRT1 in skeletal muscle ( n = 14), and had a skeletal muscle SIRT1 knockout ( n = 12) or a satellite cell SIRT1 knockout ( n = 10). Acute muscle injury was induced by injection of cardiotoxin (CTX), and phosphate‐buffered saline was used as a vector control. Plantarflexor muscle force and fatigue were evaluated before or 21 days after CTX injection. Satellite cell proliferation and mitochondrial function were also evaluated in undamaged muscles. Results: Maximal muscle force was significantly lower in control muscles of older satellite cell knockout SIRT1 mice compared to young adult wild‐type (YWT) mice ( P < 0.001). Mean contraction force at 40 Hz stimulation was significantly greater after recovery from CTX injury in older mice that overexpressed muscle SIRT1 than age‐matched SIRT1 knockout mice ( P < 0.05). SIRT1 muscle knockout models (P < 0.05) had greater levels of p53 (P < 0.05 MKO, P < 0.001 OE) in CTX‐damaged tissues as compared to YWT CTX mice. SIRT1 overexpression with co‐expression of p53 was associated with increased fatigue resistance and increased force potentiation during repeated contractions as compared to wild‐type or SIRT1 knockout models ( P < 0.001). Muscle structure and mitochondrial function were not different between the groups, but proliferation of satellite cells was significantly greater in older mice with SIRT1 muscle knockout ( P < 0.05), but not older SIRT1 satellite cell knockout models, in vitro, although this effect was attenuated in vivo after 21 days of recovery. Conclusions: The data suggest skeletal muscle structure, function, and recovery after CTX‐induced injury are not significantly influenced by gain or loss of SIRT1 abundance alone in skeletal muscle; however, muscle function is impaired by ablation of SIRT1 in satellite cells. SIRT1 appears to interact with p53 to improve muscle fatigue resistance after repair from muscle injury.